2021
DOI: 10.1111/jcmm.16882
|View full text |Cite
|
Sign up to set email alerts
|

Primary cilia in retinal pigment epithelium development and diseases

Abstract: Retinal pigment epithelium (RPE) is a highly polarized epithelial monolayer lying between the photoreceptor layer and the Bruch membrane. It is essential for vision through participating in many critical activities, including phagocytosis of photoreceptor outer segments, recycling the visual cycle‐related compounds, forming a barrier to control the transport of nutrients, ions, and water, and the removal of waste. Primary cilia are conservatively present in almost all the vertebrate cells and acts as a sensory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…These diseases are also known as ciliopathies, and although they can give rise to isolated RP, retinal defects are often linked to defects in other ciliated tissues ( 7 ). Interestingly, the RPE contains a primary cilium on its apical side, which is critical for RPE maturation and homeostasis maintenance ( 8 ), and RPE ciliary defects were recently associated with retinal ciliopathies ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…These diseases are also known as ciliopathies, and although they can give rise to isolated RP, retinal defects are often linked to defects in other ciliated tissues ( 7 ). Interestingly, the RPE contains a primary cilium on its apical side, which is critical for RPE maturation and homeostasis maintenance ( 8 ), and RPE ciliary defects were recently associated with retinal ciliopathies ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“… 136 The vascular barrier controls the exchange of molecules and ions between blood and tissues and prevents dangerous substances from entering the tissues and causing damage. 137 , 140 Primary cilia are present in the eye, i.e., retinal pigment epithelium, and they carry out sensory function through various signaling pathways. 140 , 141 Loss of primary cilia is associated with several pathologies that have anomalies in these mechanisms, such as retinopathy and Leber congenital amaurosis.…”
Section: Discussionmentioning
confidence: 99%
“… 137 , 140 Primary cilia are present in the eye, i.e., retinal pigment epithelium, and they carry out sensory function through various signaling pathways. 140 , 141 Loss of primary cilia is associated with several pathologies that have anomalies in these mechanisms, such as retinopathy and Leber congenital amaurosis. 142 , 143 In the eye, the TM also contains primary cilia and these structures change with IOP.…”
Section: Discussionmentioning
confidence: 99%
“…Since the primary cilium is necessary for the complete maturation of the RPE, it is known that RPE maturation defects in ciliopathies occur before photoreceptor degeneration [ 88 ]. PSC-RPE obtained from knockdowns of ciliary-trafficking proteins and patients with ciliopathy exhibit immaturity, impaired development of apical processes, diminished functioning, and decreased expression of adult-specific genes [ 88 , 89 ]. Although it has been shown that ciliary gene mutations in RPE are linked to ciliary defects and retinal diseases, the exact causal relationship and underlying mechanisms by which primary cilia cause RPE-related diseases are still unknown.…”
Section: Relevant Sectionsmentioning
confidence: 99%